1996
DOI: 10.1111/j.1476-5381.1996.tb15191.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of adenosine receptors in the nucleus tractus solitarius mediating hypotensive responses in the rat

Abstract: 1The aim of this study was to characterize adenosine receptors located in the nucleus tractus solitarius (NTS) that mediate decreases in blood pressure in the anaesthetized rat. To determine the adenosine receptor subtype involved, a range of selective agonists and antagonists were studied and their relative potencies evaluated. 2 The rank order of agonist potency in inducing decreases in diastolic blood pressure was N6-3 The hypotensive action of CPA following microinjection into the NTS was antagonized by i.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
1
16
0
2
Order By: Relevance
“…Previous studies have shown that stimulation of NTS A 1 receptors evokes variable hemodynamic effects: it usually increases MAP in a dose-dependent manner, whereas HR slightly decreases (1); however, the depressor effects also have been reported (36). There is also evidence that adenosine A 1 receptors located in the NTS and rostral ventrolateral medulla play a role in hypothalamic defense response facilitating the pressor component (30,31).…”
mentioning
confidence: 99%
“…Previous studies have shown that stimulation of NTS A 1 receptors evokes variable hemodynamic effects: it usually increases MAP in a dose-dependent manner, whereas HR slightly decreases (1); however, the depressor effects also have been reported (36). There is also evidence that adenosine A 1 receptors located in the NTS and rostral ventrolateral medulla play a role in hypothalamic defense response facilitating the pressor component (30,31).…”
mentioning
confidence: 99%
“…Activation of adenosine A 1 receptors produces negative inotropy, chronotropy and dromotropy, inhibition of renin release and inhibition of catecholamine release via an action in the cardiovascular control centre [6][7][8] and diuresis via reduced tubular sodium reabsorption [9]. A 2a receptor activation produces most notably dilation of coronary blood vessels [10].…”
Section: Introductionmentioning
confidence: 99%
“…NTS influences cardiovascular system. Hypotensive responses in the cardiovascular system are mediated through A 1 AR in NTS (White et al, 1996). Adenosine microinjections into the NTS result in a slow and regulated decrease in heart rate (Tseng et al, 1995;Phillis et al, 1997;Ho et al, 2008).…”
Section: Significance Of Adenosine On Dietary Restriction Induced Hypmentioning
confidence: 99%